Flood-Irrigated Corn Cost-Return Budget - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1996)
This publication projects a budget that reflects expected income and costs based on flood-irrigated corn production.
MF578_1996_10
Keywords: MF578; Economics; Crops; MF